Ar flow-rate effect for low-resistivity Al/Ti/Al Ohmic contact to n-ZnO thin films - Feri Adriyanto (Journal of Electrical, Electronic, Information, and Communication Technology, 2019)
The Ar flow rate effect on the electrical and optical properties of the sputtered Al-doped ZnO thins films were investigated. It was shown that a strong X-ray peak from (002) and (004) planes is dominant, suggesting that most grains have c-axis perpendicular to the substrate surface. The (002)-ZnO and (004)-ZnO peaks were measured at 2q = 34.120, and 71.850, respectively. It was also found that the growth rate of the Al-doped ZnO thin films increases when the sputtering power is increased. The transmittance of these film are strongly dependent on the sputtering power with the maximum transmittance of 92% was obtained at the sputtering power of 150 W and 50 sccm of Ar flow rate. The resistivity of the films is decreases as the Ar flow rate is increased. The lowest resistivity of 9.74 x 10-4 W.cm was obtained at the films with Ar flow rate of 80 sccm. The mobility increases with the Ar flow rate increases. The carrier concentration also indicates the same pattern as the mobility. The transmittance of Al-doped ZnO thin films is also strongly dependent on the Ar flow rate. It was also observed the variation of contact resistivity of Al/Ti/Al to Al-doped n-ZnO thin films. The speciﬁc contact resistivity rc of 1.8x10−5 W.cm2 was obtained at 150 nm-thick Al.